THE EFFECTS OF LEARNING ACTIVITY MANAGEMENT USING COGNITIVELY GUIDED INSTRUCTION AND QUESTIONING TECHNIQUES TO ENHANCE MATHEMATICAL PROBLEM SOLVING ABILITY ON SIMILARITY FOR MATHAYOMSUKSA THREE STUDENTS - Onngen, Patchariya; Chuntra, Chanon; Ugsonkid, Songchai (Journal of Educational Review Faculty of Education in MCU, 2025)
The purposes of this research were 1) to study the characteristics of learning activities on similarity for Mathayomsuksa three students using cognitively guided instruction and questioning techniques to enhance mathematical problem-solving ability, and 2) to study the mathematical problem-solving ability on similarity of Mathayomsuksa three students using cognitively guided instruction and questioning techniques. The sample in this research consisted of 38 Mathayomsuksa three students of one classroom who were studying in the second semester of the academic year 2024 at Tharua “nittayanukul” school that was selected by cluster random sampling from 10 classrooms. The research instruments included 10 mathematics lesson plans on similarity using cognitively guided instruction and questioning techniques, and a mathematical problem-solving ability test on similarity for Mathayomsuksa three students which was a subjective test consisting of 4 items that required students to show their solutions. The data were analyzed in term of percentage, mean, standard deviation, and t-test statistics. The research finding revealed that 1) the characteristics of learning activities on similarity using cognitively guided instruction and questioning techniques to enhance mathematical problem-solving ability consisted of 4 steps: (1) presenting the problem, (2) analyzing data and solving the problem, (3) presenting ideas and solution, and (4) discussing the solution. The roles of the teacher in conducting the learning activities included presenting problem situations to students, observing students’ behaviors during the activities to provide guidance, facilitating the use of media, equipment, and tools, using questions to stimulate analytical thinking in the problem-solving process, and the teacher also encouraged students to engage in knowledge exchange and collaborative discussions. The roles of the students were to analyze the problem situations, seeking problem solving strategies individually or collaboratively, participating in presentations, exchanging knowledge, expressing opinions, and engaging in discussions to reach conclusions. And 2) students had mathematical problem-solving ability on similarity after receiving the learning activities using cognitively guided instruction and questioning techniques were higher than the 60 percent criterion at the .05 level of significance.